Prevention and treatment of mastitis in dairy cows with bacteriocins produced by Enterococcus faecalis - Davidse, Elton (Elton Kurt) (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2003.